Facilitating Activity and Self-management for people with Arthritic knee, hip or lower back pain (FASA): A cluster randomised controlled trial. (December 2020) - Walsh, Nicola; Jones, Louise; Phillips, Sonia; Thomas, Rachel; Odondi, Lang'o; Palmer, Shea; Cramp, Fiona; Pollock, Jon; Hurley, Mike
Abstract: Background: Chronic musculoskeletal pain including osteoarthritis (OA) can significantly limit the functional independence of individuals. The spine and hip and knee are predominantly affected; management guidelines for each recommend exercise and education to support self-management. Objectives: This study investigated the effectiveness of a generic exercise and self-management intervention for people over-50 with hip/knee OA and/or lower back pain compared to continued GP management. Design: Single blind, cluster randomised controlled trial. Method: Participants who had previously consulted with hip/knee OA and/or chronic lower back pain were recruited from 45 GP practices in SW England. Practices were randomly allocated to receive continued GP care (control) or continued GP care and a 6-week group exercise and self-management intervention facilitated by a physiotherapist and located in a community-based physiotherapy department. The primary outcome measure was the Dysfunction Index of the Short Musculoskeletal Functional Assessment (DI-SMFA) measured at six month post-rehabilitation. Results: 349 participants were recruited and allocated to the intervention (n = 170) or control (n = 179) arms; the attrition rate was 13% at the 6 month primary end-point. One minor adverse event in the intervention group that required no medical input was reported. Intervention arm participants reported better function at 6 months compared with continued GP management alone (−3.01 difference in DI-SMFA [95%CI -5.25, −0.76], p = 0.01). Conclusions: A generic exercise and self-management intervention resulted in statistically significant changes in function after six-months compared with GP management alone, but clinical significance of these findings is less clear. This may be an effective way of managing group interventions for lower limb OA and chronic lower back pain. Highlights: FASA results in a statistically significant improvement in function. Clinical significance is less clear and requires further investigation. This generic exercise and education programme may be a viable clinical option.